Service life of concrete strutures rehabilitated with polymers - Aguiar, J. L. Barroso de (2010)
The service life prediction of concrete rehabilitation works is nowadays more and more significant. The rehabilitation techniques appeared as a need to solve problems posed by the degradation of concrete structures. Some years ago the rehabilitation techniques were not widespread developed and it was important to find effective and economic solutions for the problems. Now, there is more preoccupation with the service life of concrete rehabilitation techniques, like external strengthening with FRP, increase of concrete sections or reinforcement of cracked sections. The service life increase started with the quality of the concrete rehabilitation works. This inc1udes the quality of the design, the products and the execution. Some standards are now available and establish specifications for concrete rehabilitation works. This work presents the main questions related with this subject. The use of polymers in concrete rehabilitation imposes a different analysis related with durability.